From tetraploid to diploid, a pangenomic approach to identify genes lost during synthetic diploidization of Eragrostis curvula - Carballo, Jose; Bellido, Andrés Martin; Selva, Juan Pablo; Zappacosta, Diego; Gallo, Cristian Andres; Albertini, Emidio; Caccamo, Mario; Echenique, Viviana (Frontiers in Plant Science, 2023)
Introduction In Eragrostis curvula, commonly known as weeping lovegrass, a synthetic diploidization event of the facultative apomictic tetraploid Tanganyika INTA cv. originated from the sexual diploid Victoria cv. Apomixis is an asexual reproduction by seeds in which the progeny is genetically identical to the maternal plant. Methods To assess the genomic changes related to ploidy and to the reproductive mode occurring during diploidization, a mapping approach was followed to obtain the first E. curvula pangenome assembly. In this way, gDNA of Tanganyika INTA was extracted and sequenced in 2x250 Illumina pair-end reads and mapped against the Victoria genome assembly. The unmapped reads were used for variant calling, while the mapped reads were assembled using Masurca software. Results The length of the assembly was 28,982,419 bp distributed in 18,032 contigs, and the variable genes annotated in these contigs rendered 3,952 gene models. Functional annotation of the genes showed that the reproductive pathway was differentially enriched. PCR amplification in gDNA and cDNA of Tanganyika INTA and Victoria was conducted to validate the presence/absence variation in five genes related to reproduction and ploidy. The polyploid nature of the Tanganyika INTA genome was also evaluated through the variant calling analysis showing the single nucleotide polymorphism (SNP) coverage and allele frequency distribution with a segmental allotetraploid pairing behavior. Discussion The results presented here suggest that the genes were lost in Tanganyika INTA during the diploidization process that was conducted to suppress the apomictic pathway, affecting severely the fertility of Victoria cv.